Impact of Tablet Burden and Antiretroviral Therapy (ART) Choice on Virologic Outcomes in Treatment Naive HIV+ Individuals Attending an Inner City Clinic. (4th October 2017) - Markowitz, Norman; Tidwell, Beni; Lamerato, Lois; Zelt, Susan; D'Amico, Ronald; Schulman, Kathy
Abstract: Background: The durability and effectiveness of single tablet regimens (STR) in treating ART naïve patients in real world, inner city settings, has not been well established. Methods: Data was abstracted from administrative/medical records at Henry Ford Health System, serving metropolitan Detroit, for HIV+ patients initiating ART (1/1/2007–9/30/2015), who were enrolled in the Health Alliance Plan (HAP) or had ≥1 clinician contact per year and ≥1 viral load (VL)/CD4 test result ≤90 days prior to ART initiation. Patients were followed from initiation to first of: change in ART, death, HAP disenrollment, study end (03/31/2016), or lost to follow-up. Cox regression estimated impact of tablet burden on ART regimen duration, achievement of viral suppression (VS) and viral failure—(VF) failure to suppress plasma HIV RNA to <50 copies/mL or rebound after VS. Results: Among 390 eligible patients, 79% were male, 74% African-American. Median (IQR) age was 37 years (27–47), 49% MSM and 22% presented with AIDS. The majority (65%) initiated on an STR; 35% on multiple tablet regimens (MTR). The majority of STR initiators (63%) began with EFV/FTC/TDF; 24% with EVG/c/FTC/TDF; and 8% with DTG/ABC/3TC. The most frequent MTR were DRV+RTV+TDF/FTC (26%) and ATV+RTV+TDF/FTC (20%). Median (IQR) log10 VL at baseline was 4.8 (4.3–5.2) in STR; 4.8 (4.4–5.4) in MTR cohorts. Median CD4 cells/µL (IQR) was 277 (115–407) in STR; 231 (37–371) in MTR. VL suppression occurred in 81% (85% STR, 74% MTR, P < 0.01) of patients and in 91% of INSTI regimens (91% STR, 90% MTR, P = 0.757).VF occurred in 19% (15% STR, 25% MTR, P = 0.015) and in 10% of INSTI regimens (9% STR, 13% MTR, P = 0.459). Resistance occurred in 15% of VF patients, predominantly with NNRTI mutations. A total of 22% of STR and 60% of MTR initiators experienced a change in their initial ART regimen ( P < 0.0001). Cox model results suggest STR initiators were 59% less likely to experience regimen change ( P < 0.0001), 46% less likely to experience VF ( P < 0.05) and 30% more likely to achieve viral suppression ( P < 0.05) compared with MTR initiators. Conclusion: Inner city, HIV treatment naïve patients, initiating ART with a STR are significantly more likely to achieve viral suppression and less likely to experience a change in ART regimen. Disclosures: B. Tidwell, ViiV Healthcare: Research Contractor, Research support; L. Lamerato, ViiV Healthcare: Collaborator, Research support; S. Zelt, ViiV Healthcare: Employee and Shareholder, Salary and Stock; R. D'Amico, ViiV Healthcare: Employee and Shareholder, Salary and Stock; K. Schulman, ViiV Healthcare: Research Contractor, Research support